Pelatihan Pembuatan Laporan Akuntansi Perpajakan Pada Forum Pengusaha Kuliner Jogja - Suwandi, Eko Darmawan (JCSE: Journal of Community Service and Empowerment, 2022)
The target to be achieved in this service program is to help make tax accounting reports for UMKM who are members of the "Forum Pengusaha Kuliner Jogja". This service is also carried out to increase the understanding of culinary taxpayers about accounting and tax issues, especially in the culinary field. The culinary business sector will be distinguished in the non-restaurant sector and in the restaurant sector. These fields have different calculation methods because they relate to the amount of turnover and applicable laws. The final result of this training is expected to increase knowledge in the field of accounting and taxation while at the same time encouraging training participants to comply with tax laws and applicable regulations. In this training, service participants are able to apply tax calculations and tax regulations, including Final Income Tax, Article 25 Income Tax. , PPh article 21, taxation fiscal financial reports and of course the procedures for paying taxes